Genotypic and phenotypic spectrum of infantile liver failure due to pathogenic TRMU variants - Vogel, Georg; Mozer-Glassberg, Yael; Landau, Yuval E.; Schlieben, Lea D.; Prokisch, Holger; Feichtinger, René G.; Mayr, Johannes A.; Brennenstuhl, Heiko; Schröter, Julian; Pechlaner, Agnes; Alkuraya, Fowzan S.; Baker, Joshua J.; et al. (Genetics in medicine, 2023)
Purpose - This study aimed to define the genotypic and phenotypic spectrum of reversible acute liver failure (ALF) of infancy resulting from biallelic pathogenic TRMU variants and determine the role of cysteine supplementation in its treatment. - Methods - Individuals with biallelic (likely) pathogenic variants in TRMU were studied within an international retrospective collection of de-identified patient data. - Results - In 62 individuals, including 30 previously unreported cases, we described 47 (likely) pathogenic TRMU variants, of which 17 were novel, and 1 intragenic deletion. Of these 62 individuals, 42 were alive at a median age of 6.8 (0.6-22) years after a median follow-up of 3.6 (0.1-22) years. The most frequent finding, occurring in all but 2 individuals, was liver involvement. ALF occurred only in the first year of life and was reported in 43 of 62 individuals; 11 of whom received liver transplantation. Loss-of-function TRMU variants were associated with poor survival. Supplementation with at least 1 cysteine source, typically N-acetylcysteine, improved survival significantly. Neurodevelopmental delay was observed in 11 individuals and persisted in 4 of the survivors, but we were unable to determine whether this was a primary or a secondary consequence of TRMU deficiency. - Conclusion - In most patients, TRMU-associated ALF was a transient, reversible disease and cysteine supplementation improved survival.
Online verfügbar: 29. Oktober 2022, Artikelversion: 2. Juni 2023
Gesehen am 08.08.2023